Plant-hummingbird interactions and temporal nectar availability in arestinga from Brazil - LORENA C.N. FONSECA; JEFERSON VIZENTIN-BUGONI; ANDRÉ R. RECH; MARIA ALICE S. ALVES (Anais da Academia Brasileira de Ciências, 2015)
ABSTRACT Hummingbirds are the most important and specialized group of pollinating birds in the Neotropics and their interactions with plants are key components to many communities. In the present study we identified the assemblage of plants visited by hummingbirds and investigated the temporal availability of floral resources in an area of restinga, sandy plain coastal vegetation associated with the Atlantic forest, in Southeastern Brazil. We recorded flower and nectar features, flowering phenology and interactions between plants and hummingbirds and estimated the amount of calories produced per hectare from June 2005 to August 2006. Ten plant species were visited by two hummingbirds,Amazilia fimbriata and Eupetomena macroura. Resource availability was highly variable among plant species and over time. Nectar volume and concentration per flower were similar to other Neotropical hummingbird-visited plant assemblages. The estimated nectar resource availability between months varied from 0.85 to 5.97 Kcal per hectare/day, demanding an area between one and 6.8 ha to support a single hummingbird. Our study reports an unusual tropical setting where almost all interactions between hummingbirds and plants were performed by a single hummingbird species,A. fimbriata. Hence, the variable nectar availability is probably influencing hummingbird movements, its foraging area, and consequently plant pollination.